The significance of mixed chimaerism and cell lineage chimaerism monitoring in paediatric patients post haematopoietic stem cell transplant. (14th April 2022) - Kricke, Susanne; Rao, Kanchan; Adams, Stuart
Abstract: Haematopoietic stem cell transplants (HSCTs) are carried out across the world to treat haematological and immunological diseases which would otherwise prove fatal. Certain diseases are predominantly encountered in paediatric patients, such severe primary immunodeficiencies (PID) and diseases of inborn errors of metabolism (IEM). Chimaerism testing for these disorders has different considerations compared to adult diseases. This review focuses on the importance of cell‐lineage‐specific chimaerism testing and examines the appropriate cell populations to be assessed in individual paediatric patient groups. By analysing disease‐associated subpopulations, abnormalities are identified significantly earlier than in whole samples and targeted clinical decisions can be made. Chimaerism methods have evolved over time and lead to an ever‐increasing level of sensitivity and biomarker arrays to distinguish between recipient and donor cells. Short tandem repeat (STR) is still the gold standard for routine chimaerism assessment, and hypersensitive methods such as quantitative and digital polymerase chain reaction (PCR) are leading the forefront of microchimaerism testing. The rise of molecular methods operating with minute DNA amounts has been hugely beneficial to chimaerism testing of paediatric samples. As HSCTs are becoming increasingly personalised and risk‐adjusted towards a child's individual needs, chimaerism testing needs to adapt alongside these medical advances ensuring the best possible care.